KEPATUAHAN DAN RESPON CALON JAMAAH HAJI LAMPUNG TERHADAP PERATURAN PENYELENGGARAAN IBADAH HAJI DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI LAMPUNG TAHUN 2022 - Siti Zulaikha (Institut Agama Islam Negeri Metro, 2022)
The purpose of this study is to analyze the compliance and response of prospective pilgrims in Lampung province to the regulations for organizing the pilgrimage. This research is qualitative research with a field research approach. The results of the research show that the activities of organizing the hajj deal with various agencies in both Indonesia and Saudi Arabia. Therefore, carrying out the pilgrimage is required in addition to material and physical abilities (istito'ah), it also requires patience. Be patient with the decisions of Allah SWT, and be patient with the decisions of the Indonesian government which follow the decisions of the Saudi Arabian government.